1986
DOI: 10.1016/0035-9203(86)90191-4
|View full text |Cite
|
Sign up to set email alerts
|

A study of head lice among primary schoolchildren in Kenya

Abstract: Of 1270 schoolchildren (651 girls and 619 boys) from 33 urban and rural primary schools in different regions of Kenya who were examined for head lice, 17.1% were infested (8% with living lice or nits, 9.1% with dead nits). The over-all difference between infestation rates in urban and rural schools was not significant, but there was considerable variation in the five different regions selected. Infestation was not sex-related. Infestation rates tended to be higher in older children and in children with longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 10 publications
3
14
1
Order By: Relevance
“…The absence of significant differences between the prevalence rates of pediculosis in schoolchildren from rural and urban area (Table I) are in agreement with Chunge (1986). Nevertheless, other surveys have verified significant differences between head lice distribution found in urban and rural schoolchildren (Donaldson 1976, Hoffmann 1983, Ogunridade & Oyejide 1984.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The absence of significant differences between the prevalence rates of pediculosis in schoolchildren from rural and urban area (Table I) are in agreement with Chunge (1986). Nevertheless, other surveys have verified significant differences between head lice distribution found in urban and rural schoolchildren (Donaldson 1976, Hoffmann 1983, Ogunridade & Oyejide 1984.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, those authors categorized the children as whites and brunets (including dark brunets, mulattos and blacks) and now the children were separated into blacks and non-blacks (including dark brunets, brunets and whites). Lowers head lice prevalences generally encountered in blacks would be due to the differences in shape of hair between races (Ashcroft 1969, Chunge 1986. Results found in the present study indicate that, as other studied factors, the shape of hair is not preponderant in the installation of head lice in the studied population.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…But, the magnitude of this needs to be confirmed through appropriate scientific study. Other studies have found that family size, overcrowding and sleeping in the same bed can promote transmission [24][25][26][27][28].…”
Section: Bedding As a Source Of Head Licementioning
confidence: 99%